EXTH-67. PHARMACOLOGIC INHIBITION OF LYSINE SPECIFIC DEMETHYLASE-1 (LSD1) AS AN ADJUVANT IMMUNE-SENSITIZATION STRATEGY IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (9th November 2020) - Bailey, Cavan; Collier, Tiara; Henry, Verlene; Monje, Michelle; Nazarian, Javad; Lee, Dean; Wang, Linghua; Gopalakrishnan, Vidya; Becher, Oren; Chandra, Joya
Abstract: Diffuse midline gliomas (DMG), including brainstem DIPG (diffuse intrinsic pontine glioma), are incurable pediatric brain tumors. Mutations in the H3 histone tail (H3.1/3.3-K27M) are a feature of DIPG, highlighting epigenetic aberrations in these tumors. Lysine specific demethylase-1 (LSD1), is an enzyme that acts upon mono and di-methylated histone H3K4/K9, and pharmacological inhibitors of its enzymatic and scaffolding domains are clinically viable. Patient-derived DIPG cell lines, orthotopic mouse models, and pediatric high-grade glioma (pHGG) datasets were used to evaluate effects of LSD1 inhibitors on cytotoxicity and immune gene expression. Because an unique immune signature was sen with enzymatic LSD1 inhibitors in DIPG cells in vitro, immune cell cytotoxicity was assessed in DIPG cells pre-treated with LSD1 inhibitors and informatics platforms were used to determine immune infiltration of pHGG. Selective cytotoxicity and an immunogenic gene expression signature was established in DIPG cell lines and in brainstem tumor-bearing mice using clinically-relevant LSD1 inhibitors. Pediatric HGG patient sequencing data demonstrated survival benefit using this LSD1-dependent gene expression signature. On-target binding of catalytic LSD1 inhibitors was confirmed in DIPG and pre-treatment of DIPG with these inhibitors increased lysis by natural killer (NK) cells. CIBERSORT analysis of patient data confirmed NK infiltration is beneficial to patient survival while CD8 T-cells are negatively prognostic. Catalytic LSD1 inhibitors are non-perturbing to NK cells while scaffolding LSD1 inhibitors are toxic to NK cells and do not induce the gene expression signature in DIPG cells. Treatment of orthotopic xenograft bearing DIPG mouse models with catalytic LSD1 inhibitors and NK cells showed a significant reduction in tumor burden. In summary, we find that LSD1 inhibition using catalytic inhibitors is both selectively cytotoxic and promotes a functional immune gene expression signature that is associated with NK cell killing, representing a therapeutic opportunity for pHGG.